2010
DOI: 10.1113/expphysiol.2010.054221
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Physiology –Research Paper: Exercise training combined with angiotensin II receptor blockade reduces oxidative stress after myocardial infarction in rats

Abstract: An increase in oxidative stress and decrease in antioxidant enzymes have been suggested to be involved in the pathophysiology of myocardial infarction (MI). In this study in rats, treadmill exercise training and losartan treatment began 1 week post-myocardial infarction (MI) and lasted 8 weeks. We evaluated the changes in the mRNA and protein expressions for the enzymatic antioxidants superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase after exercise and losartan treatment post-MI. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…[53] As shown in Figure 3, the expression of catalase increased only in the trained group compared to the OVX group. Consistent with our findings, Kang et al [11] reported no changes in the coronary expression of catalase in response to ERT, and Xu et al [54] reported enhanced catalase expression and activity in cardiac muscle after exercise training in rats submitted to myocardial infarction.…”
Section: Discussionsupporting
confidence: 92%
“…[53] As shown in Figure 3, the expression of catalase increased only in the trained group compared to the OVX group. Consistent with our findings, Kang et al [11] reported no changes in the coronary expression of catalase in response to ERT, and Xu et al [54] reported enhanced catalase expression and activity in cardiac muscle after exercise training in rats submitted to myocardial infarction.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported that exercise and losartan mediated their eVects diVerently, with losartan further unloading the hemodynamic burden of the heart, and exercise training increasing metabolic enzyme activity, particularly creatine and adenylate kinase activities (Kemi et al 2007). Exercise plus losartan treatment has also been shown to improve catalase and MnSOD expression in the post-infarcted heart (Xu et al 2010). Thus, there are a host of reported hemodynamic and metabolic beneWts associated with exercise training and AT1 receptor blockade.…”
Section: Discussionmentioning
confidence: 97%
“…Losartan can also prevent the increased concentration of H 2 O 2 caused by Ang II infusion [21]. In addition, it was shown that eight-week Losartan treatment leads to an increase of CAT activity in damaged cardiac tissue of Sprague-Dawley rats [22]. It is well-known that hydroxyl radical, one of the most reactive oxygen species, as a product of H 2 O 2 degradation (Fenton's reaction), has an important role in LP, but CAT decomposes H 2 O 2 to both electro-neutral H 2 O and O 2 molecules.…”
Section: Discussionmentioning
confidence: 99%